A study on internet banking in Turkey - Tonguç, Erdal (My University, 2000)
Bu tezi üç ana bölüme ayırabiliriz. Çalışmanın ilk bölümünde İnternet'in finansal servisler amacıyla ne derece ve nasıl kullanılabileceği incelenmiştir. Elektronik bankacılık ve elektronik para hareketlerinin risk yönetimi, bankacılık yönetimi perspektifinden tartışılmıştır. Potansiyel riskler tanımlanmış, incelenmiş ve gruplanmıştır. Risklerin tanımı ve incelenmesi doğrultusunda, risk yönetimi sürecinde bankaların atması gereken başlıca adımlar özetlenmiştir. İkinci bölüm, Internet Bankacılığı ile ilgili haberdarlık, kullanım ve tüketici tutumlarını ölçmeye yönelik, İstanbul'da 210 kişi ile yapılan bir saha çalışmasını içermektedir. Çalışmanın temel amacı, tüketicilerin yeni bir dağıtım kanalı olan İnternet Bankacılığı'na karşı olan tutum ve davranışlarını belirlemekle beraber, haberdarlık düzeyini ölçmek ve Türkiye'de İnternet bankacılığının nasıl kavrandığını ortaya koymaktır. Buna ek olarak, belli başlı İnternet bankacılığı ürünlerinin kullanım sıklığı da ölçülmüştür. Çalışmanın son bölümü, saha çalışmasının

bulguları ve bu bulgularla ilgili varılan sonuçları içermektedir, ayrıca bu konuda gelecekte yapılacak araştırmalara yardımcı olacak noktalar ve yönetimsel tavsiyelerde yeralmaktadır. This thesis can be distinguished into three major parts. In the first section of the study, we examined in what respect and how the Internet is used and can be used for the purposes of financial services. The risk management of electronic banking and electronic money activities from a banking supervisory perspective is discussed. The possible risks are identified, analysed and categorised. Based on the identification and analysis of risks, the major steps in a risk management process for banks engaging in electronic banking is outlined. The second part includes a field survey conducted with 210 respondents to gather information about the awareness, usage and attitudes towards Internet banking services in Istanbul. The primary objective of this study is to discover attitudes and behaviours along with the awareness of consumers towards a new distribution channel Internet banking as well as to gain insight about Internet banking in Turkey. Additionally the specific Internet banking services, and their usage frequencies will be investigated. In the last section of the thesis the summary of major findings about the study of Internet Banking services and the concluding remarks about these findings will be presented. Some offers for policy implications with a need for further research will also be added in this section.
Keywords: BANKACILIK; İNTERNET